Modelling of accidents on two-lane single carriageway roads in Malaysia - Mohd Marjan, Jamilah (2011)
Road safety management in Malaysia comprises implementation of road safety auditing, blackspot treatment, maintenance management and the safe system approach road assessment programme. All these efforts are implemented on two-lane carriageway roads where a high percentage of accidents occur. Currently the interventions are based on guidelines from developed countries and studies from local research. The purpose of this research is to develop accident prediction models with respect to traffic and road geometry on a two-lane single carriageway road network. This research focused on modeling accident rates in relation to various categories of roadway conditions. The models derived would be used by engineers to guide them in making choices in terms of road safety enhancement to the road network. This research was carried out in the State of Selangor on the Federal trunk roads and it was a representative of Federal road network in the country in terms of conditions and environment. The research was focused on accidents along a two-lane single carriageway road. Traffic and geometric data were collected, analysed and modelled using the GENSTAT software. Poisson regression was used in the modeling of accidents; which is the common method in analysing accident data. Two groups of model were developed. The ’Engineers’ models’ were developed for the use of practicing engineers in the region and the ‘HDM models’ developed for the use of road managers in accident prediction and economic analysis in the maintenance management HDM4 system. These models are very useful to compute accident cost savings with the implementation of specific infrastructure improvement. It was found that different explanatory variables affect differently for different types of accidents. Total and damage accidents were very similar, while casualty and injury accidents resulted in different variables in the models developed. Casualty is fatal and injury accidents combined in this research. Fatal accident model was the most difficult to model as most of the variables were not significant in explaining fatal accidents. The ‘Engineers’ models’ and the ‘HDM models’ are very similar in the fact that the variables that had a significant effect on total, damage, casualty, injury and fatal accident were similar in both models.